La Aplicación De Herramientas Didáctica En El Aula De Clase “Interactive Physics” Y Su Incidencia En El Rendimiento Académico Estudio De Caso: Estudio De Las Leyes De Newton - Marco Hjalmar Velasco Arellano; Carla Sofía Arguello Guadalupe; Oswaldo Geovanny Martínez Guashima; Carmen Cecilia Mejía Calle; Hugo Humberio Paz León (European Scientific Journal, ESJ, 2017)
This research work seeks to find out the incidence that the educative software called Interactive Physics has on the students’ academic performance. The experiment will consider students who are studying their first semester in the Agronomy School, classroom “1”, at the Natural Resources College of ESPOCH. The class will be divided in two subgroups with whom an interactive simulator program will be used and it will allow students to develop skills within the collaborative learning method of Physics, specifically, the Newton’s Laws. The hypothesis is the following: making and applying the guideline called Dynamic by using the Interactive Physics influences the first semester Agronomy students’ academic performance. The above mentioned dynamic guide was used in one of the groups in order to analyze their academic performance. The other group did not use it. Then, through the statistical Chi-Squared test and the Normalized Z-score, the existence of high correlation concerning the students’ academic performance when using the didactic guide Interactive Physics was evidenced. As a conclusion it can be said that the use of this methodology improves students’ academic performance.